(untitled) (Conferencea, 2023)
Monitoring analysis of the results of the survey of physical education specialists allowed to expand the range of goals and objectives that affect the improvement of the content and methods of teaching secondary school students in the process of physical education lessons and organized sports and recreation activities in the daily routine of rural school educational institutions.